Photonics-Assisted Non-Scanning High-Accuracy Frequency Measurement Using Low-Speed Components - Zhiqiang Shen; Chenfei Jin; Qunsong He; Zijing Zhang; Yuan Zhao (IEEE Photonics Journal)
Instantaneous frequency measurement of microwave signals is a fundamental functionality for applications including radar and electronic warfare. Photonic techniques have potential to enlarge the measurable frequency range, however, most of photonics-assisted solutions are lack of the ability to simultaneously achieve large measurement range, high measurement speed, and high measurement accuracy in a single system. Here, we propose a photonics-assisted nonscanning high-accuracy multiple frequency measurement scheme based on optical beating between double sideband carrier-suppressed signals and a detuning optical frequency comb at a narrow band photodiode. The frequencies of the incoming RF signals can be estimated by analyzing the frequency and power information of the beating notes. In a proof-of-principle experiment, single- and multiple-frequency measurements with a large measuring range from 2 to 12 GHz and low measuring error of less than 2 MHz was achieved. This scheme is suitable for instantaneous multiple-frequency measurement with high accuracy across a large frequency measurement range.